2017 IEEE 14th International Symposium on Biomedical Imaging (ISBI 2017) 2017
DOI: 10.1109/isbi.2017.7950566
|View full text |Cite
|
Sign up to set email alerts
|

A novel framework for groupwise registration of fMRI images based on common functional networks

Abstract: Accurate registration plays a critical role in group-wise functional Magnetic Resonance Imaging (fMRI) image analysis, as spatial correspondence among different brain images is a prerequisite for inferring meaningful patterns. However, the problem is challenging and remains open, and more effort should be made to advance the state-of-the-art image registration methods for fMRI images. Inspired by the observation that common functional networks can be reconstructed from fMRI image across individuals, we propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Many studies (3; 4; 5) have found that a range of neuroimaging biomarkers can be used to diagnosis both AD and SMC. Structural magnetic resonance imaging (sMRI) is a noninvasive method that can detect high-resolution structural changes in the brain caused by atrophy, such as changes in thickness, volume, shape, and texture (8). Similarly, 18-Fluoro-Deoxy-Glucose Positron Emission computed Tomography (FDG-PET) uses radioactive tracers to track cerebral metabolic rate of glucose reflecting hemodynamic and detect changes in brain function (7).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies (3; 4; 5) have found that a range of neuroimaging biomarkers can be used to diagnosis both AD and SMC. Structural magnetic resonance imaging (sMRI) is a noninvasive method that can detect high-resolution structural changes in the brain caused by atrophy, such as changes in thickness, volume, shape, and texture (8). Similarly, 18-Fluoro-Deoxy-Glucose Positron Emission computed Tomography (FDG-PET) uses radioactive tracers to track cerebral metabolic rate of glucose reflecting hemodynamic and detect changes in brain function (7).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Deep learning methods have demonstrated excellent performance on high-dimensional complex data, and have been widely applied to the diagnosis of AD (8). These methods typically involve three basic steps: 1) identifying regions of interest (ROI), 2) extracting features, and 3) constructing classification models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ulti-modal medical imaging plays an important role in many clinical applications [1][2][3][4][5][6][7][8][9][10][11], such as image-guided intervention, disease diagnosis, and treatment planning. Among them, multi-contrast magnetic resonance (MR) imaging is one of the most prevalent techniques utilized in brain imaging as different MR imaging sequences can highlight different regions of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Here we explore an alternative to this approach in which we use a topologically-constrained nonrigid deformation of the cortical surfaces to perform inter-subject registration. An alternative recent method also used rfMRI data for this purpose [7]. In that case, z-score maps derived from ICA analysis of the functional activations were used to perform group-wise cortical surface registration.…”
Section: Introductionmentioning
confidence: 99%